Analysis of Spatial Ability in terms of High Self Efficacy - Saipullah, Muhammad; Anwar, Azwar; Hermansyah, Hermansyah (Journal of Mathematics and Applied Statistics, 2023)
This research was conducted to find out and describe how students' spatial abilities are viewed from high self efficacy. The type of research used is qualitative with a case study approach. The subjects in the study were students with high questionnaire results from the questionnaire categorization results. The technique of taking subjects is purposive sampling, before choosing the subject the researcher gives self efficacy questionnaire to all students of class VIII Al-Qalam. Furthermore, the questionnaire was categorized, then obtained three subjects with high self efficacy. Researchers collected data with questionnaires, document analysis and interviews. In this study the researcher acts as the main instrument, while the supporting instruments of this study are questionnaires, interviews and documents. The data analysis technique used in this research is by collecting data, reducing data, presenting data, and drawing conclusions. The data validity test used is credibility test, transfebility test, dependability test, and confirmablity test. The results showed that each subject with high self efficacy has different and similar characteristics in answering spatial ability questions. All subjects can fulfill the spatial ability indicators well. So it can be concluded that subjects with high self efficacy are able to fulfill spatial ability indicators and have good spatial abilities.